Digital Activism Practices of Pelita Padang Community in Voicing Diversity Issues Through Instagram @pelita.padang - AB Sarca Putera; Ayu Adriyani; Amin Akbar; Muhammad Al Fikrah Firlian (Communicatus: Jurnal Ilmu komunikasi, 2024)
The Setara Institute for Democracy and Peace places Padang City on the list of 10 cities with the lowest tolerance levels from 2017 to 2023. This reflects that the city government's efforts to maintain diversity have not been optimal. Therefore, reflection is needed, one of which is through information technology to encourage the birth of digital activism. This study examines the social situation that triggers activism, especially in the digital space, and the optimization of digital platforms in supporting the movement. The study used a qualitative descriptive method through semi-structured interviews and document analysis. Data were analyzed from content uploaded by the Pelita Padang Community on Instagram @pelita.padang. The study results show that Indonesia's political and social dynamics mainly drive Pelita Padang's activism. This community effectively combines offline and online activities to expand the reach of its movement. Social media is used as a means of education, campaigning, and collaboration, strengthening their activism's impact. In conclusion, the combination of offline and digital activism by the Pelita Padang Community has responded to the challenges of intolerance in Padang City. This approach proves that optimizing social media can be a strategic tool to strengthen solidarity and diversity in society.